Pd‐modified Au on Carbon as an Effective and Durable Catalyst for the Direct Oxidation of HMF to 2, 5‐Furandicarboxylic Acid. Issue 4 (11th March 2013) - Villa, Alberto; Schiavoni, Marco; Campisi, Sebastiano; Veith, Gabriel M.; Prati, Laura
<x xml:space="preserve">Abstract</x> Mixed noblility: We show that the modification of a gold/carbon catalyst with platinum or palladium produces stable and recyclable catalysts for the selective oxidation of 5‐hydroxymethylfurfural (HMF) to 2, 5‐furandicarboxylic acid (FDCA): the support and nanoparticle chemistry directly mediate the selective oxidation of terminal hydroxyl groups in bio‐derived HMF. This finding is a significant advance over current conversion technology because of the technological importance of FDCA.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>